1995
DOI: 10.1007/bf02360039
|View full text |Cite
|
Sign up to set email alerts
|

Influence of damage to the suprachiasmatic nuclei of the hypothalamus of rats on the dynamics of short-period fluctuations of normal and abnormal behavior

Abstract: An intensification of a swimming behavior with an increase in the proportion of active swimming and limitation of the duration of immobilization was found in rats following bilateral electrolytic destruction of the suprachiasmatic nuclei of the hypothalamus. The restructuring of the temporal dynamics of swimming is manifested in a limitation of the rhythmological index of depressivity. The animals with ablated nuclei demonstrate more pronounced behavioral disturbances in response to the introduction of fenamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 1 publication
1
12
0
Order By: Relevance
“…Thus, the authors concluded that SCN lesions have a protective effect in the induction of behavioral despair 88 . Similar conclusions were reached almost a decade earlier when Arushanyan and colleagues demonstrated reduced immobility during the forced swim test, in rats that received bilateral SCN lesions 89 . It may be difficult to draw definitive conclusions from these studies as testing of depressive-like behavior occurred during the inactive phase of the rats.…”
Section: Circadian Rhythm Disruption and Major Depressive Disordersupporting
confidence: 77%
“…Thus, the authors concluded that SCN lesions have a protective effect in the induction of behavioral despair 88 . Similar conclusions were reached almost a decade earlier when Arushanyan and colleagues demonstrated reduced immobility during the forced swim test, in rats that received bilateral SCN lesions 89 . It may be difficult to draw definitive conclusions from these studies as testing of depressive-like behavior occurred during the inactive phase of the rats.…”
Section: Circadian Rhythm Disruption and Major Depressive Disordersupporting
confidence: 77%
“…However, there is only limited evidence that SCNx animals suffer disturbed mood regulation. SCNx rats show less immobility in the forced swim test, but no impact on behavior in the social defeat paradigm (Arushanian & Popov, 1994;Tataroglu, Aksoy, Yilmaz, & Canbeyli, 2004;Tuma, Strubbe, Mocaer, & Koolhaas, 2005).…”
Section: Scnmentioning
confidence: 86%
“…Early studies investigated whether the SCN regulates mood by assessing mood-like behaviors in SCN-lesioned rats. Two groups found that lesioning the SCN resulted in less immobility in the forced swim test [ 236 , 237 ]. One interpretation is that disrupting SCN function has antidepressant effects.…”
Section: Effects Of Scn Manipulations On Mood-like Behaviors In Romentioning
confidence: 99%